2020
DOI: 10.1525/collabra.268
|View full text |Cite
|
Sign up to set email alerts
|

Is Healthy Neuroticism Associated with Longevity? A Coordinated Integrative Data Analysis

Abstract: Individual differences in the Big Five personality traits have emerged as predictors of health and longevity. Although there are robust protective effects for higher levels of conscientiousness, results are mixed for other personality traits. In particular, higher levels of neuroticism have significantly predicted an increased risk of mortality, no-risk at all, and even a reduced risk of dying. The current study hypothesizes that one potential reason for the discrepancy in these findings for neuroticism is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 89 publications
1
12
2
Order By: Relevance
“…It was especially notable to find the insignificant association between neuroticism residual variance and mortality risk, after the common variance was saturated by the internalizing fac- tor. While a number of prior studies have reported a significant connection between neuroticism and mortality risk 15,16,28 , our findings indicate that such significant effects may be largely accounted for by the common variance that neuroticism shares with other internalizing pathologies, and that neuroticism itself may not be a consistent predictor of mortality risk 63 .…”
Section: The Superior Predictive Validity Of the Transdiagnostic Internalizing Factorcontrasting
confidence: 85%
“…It was especially notable to find the insignificant association between neuroticism residual variance and mortality risk, after the common variance was saturated by the internalizing fac- tor. While a number of prior studies have reported a significant connection between neuroticism and mortality risk 15,16,28 , our findings indicate that such significant effects may be largely accounted for by the common variance that neuroticism shares with other internalizing pathologies, and that neuroticism itself may not be a consistent predictor of mortality risk 63 .…”
Section: The Superior Predictive Validity Of the Transdiagnostic Internalizing Factorcontrasting
confidence: 85%
“…Previous studies demonstrated that neuroticism could indeed be beneficial for performance because of individuals' increased tolerance for negative affect [50], which may have played a supportive role in participants' willingness to complete self-assessments in this study. These findings resemble what previous researchers have coined healthy neuroticism, where a combination of neurotic self-awareness and conscientious decision making indicates engaging in favorable health behaviors such as increased doctor visits and fewer risky behaviors such as alcohol consumption and smoking [51][52][53][54]. Importantly, Weston and Jackson [52] found that healthy neurotics were more successful than other personality types in implementing effective behavior change after disease onset, suggesting that awareness of a chronic condition facilitated healthful actions particularly well in this group.…”
Section: Principal Findingssupporting
confidence: 84%
“…On the other hand, it should not be overlooked that some studies have suggested that neuroticism may be protective against mortality. These studies have examined the possibility that certain aspects of neuroticism may be relevant as protective factors [ 31 ] or may have protective effects on health through interaction with other personality traits [ 32 ], based on Friedman’s idea of healthy neuroticism [ 33 ]. Neuroticism is positively associated with one factor of body vigilance: sensation awareness belief.…”
Section: Discussionmentioning
confidence: 99%